KUALITAS PENGALAMAN MAHASISWA DALAM MEWUJUDKAN CITRA PENGETAHUAN WEBSITE PERPUSTAKAAN UNIVERSITAS SUMATERA UTARA - Annisa Intan Zakira; Zahra Ajiziah; Erni Naomi Tigris Br Purba; Mira Jelita Hulu; Erikson Saragih (Pustakaloka, 2025)
The library website serves as a digital gateway that reflects the institution’s knowledge identity and service quality. This study analyzes the role of user experience in shaping the academic knowledge image of the University of North Sumatra (USU) Library website. Using a qualitative phenomenological research approach, data were collected through semi-structured interviews with six informants, consisting of five active students as primary informants and one library staff member as a supporting informant. Data analysis followed the interactive Miles and Huberman model, emphasizing the interpretation of users’ lived experiences. The results reveal that user experience quality, which includes usability, accessibility, design appeal, information accuracy, and responsiveness, plays an important role in shaping how users perceive the library website as a representation of academic knowledge. Furthermore, the SERVQUAL dimensions—tangibles, reliability, responsiveness, assurance, and empathy—function as an interpretative framework that connect user satisfaction with knowledge dissemination. In conclusion, the USU Library website has largely succeeded in positioning itself as a digital symbol of knowledge; however, interface optimization and more intuitive navigation structures are still needed to enhance the overall user experience.